ALAT BANTU PENDETEKSI UANG KERTAS UNTUK PENYANDANG TUNANETRA - Wiwin Sundari; Rama; Ocsirendi; Aan Febriansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Currently the use of banknotes is unavoidable. Banknotes as a transaction media has been used by all people especially adults. Not only adults, even children already know how to use several banknotesnominal, that is by looking at the color of each banknotes nominal. Therefore, it is necessary to make a banknotes detection tool for blind people so that they are able to recognize the nominal value of banknotes through a sound output system so that it can make it easier for them to transact using banknotes. As for the method used in making this final project was doing test each banknotes nominal using TCS230 color sensor to get the RGB value which is then compared to the value of of each RGB value to be entered into the Arduino Uno database as a special value to initialize each banknote nominal. Based on the results of the tests carried out that the tool made was able to detect 7 nominal banknotes, namely Rp. 1,000, Rp. 2,000, Rp. 5,000, Rp. 10,000, Rp. 20,000, Rp. 50,000, and Rp. 100,000. As for the overall examination of banknotes nominal, this tool has a success percentage of 92.8% and the error percentage on the tool is approximately 7.2%.